Edukasi Gizi dan Anemia pada Remaja Putri di Desa Menanti Kecamatan Kelekar Kabupaten Muara Enim - Prautami, Erike Septa; Sari, Indah Purnama; Yuliana, Indah; Rahmiwati, Anita; Febry, Fatmalina; Sari, Desri Maulina; Yuliarti; Ningsih, Windi Indah Fajar; Arinda, Ditia Fitri; Harwanto, Fatria; Ramadhani, Ira Dewi; Ramdika, Sari Bema; Sari, Dwi Inda (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Nutritional anemia is a condition where the hemoglobin level in the blood is below normal. Anemia education is very important because there are still many young women who do not know about anemia. This activity aims to increase knowledge about balanced nutrition and anemia among young women in Menanti Village. Methods: This activity is in collaboration with the Head of Menanti Village, Kec. Kelekar Muara Enim Regency with a total of 36 participants, using lecture and discussion methods. The activities carried out are measuring knowledge and providing education using the lecture method. Results: Nutrition and anemia education activities in Menanti Village, Kelekar District, Muara Enim Regency were carried out on Tuesday 11 June 2024 for 36 young women. Conclusion: Community service activities by lecturers at the FKM Nutrition Study Program at Sriwijaya University in the form of nutritional education regarding anemia in young women using leaflets as a medium increase female students' knowledge regarding anemia. Knowledge about applying the principles of balanced nutrition is one of the efforts to prevent anemia from an early age in adolescents.